Methylation Landscape: Targeting Writer or Eraser to Discover Anti-Cancer Drug - Zhou, Wen-min; Liu, Bin; Shavandi, Amin; Li, Lu; Song, Hang; Zhang, Jian-ye (Frontiers in Pharmacology, 2021)
Cancer is global health and a major challenge for our health system, despite the important pharmacological and therapeutic discoveries we have seen since past five decades. The increasing prevalence and mortality of cancer may be closely related to smoking, exposure to environmental pollution, dietary and genetic factors. Despite significant promising discoveries and development such as cell and biotechnological therapies a new breakthrough in the medical field is needed to develop specific and effective drugs for cancer treatment. On the development of cell therapies, anti-tumor vaccines, and new biotechnological drugs that have already shown promising results in preclinical studies. With the continuous enrichment and development of chromatin immunoprecipitation sequencing (ChIP-seq) and its derivative technologies, epigenetic modification has gradually become a research hotspot. As a key ingredient of epigenetic modification, Writers, Readers, Erasers have been gradually unveiled. Cancer has been associated with epigenetic modification especially methylation and therefore different epigenetic drugs have been developed and some of those are already undergoing clinical Phase I or Phase II trials, and it is believed that these drugs will certainly assist the treatment in the near future. With respect to this, an overview of anti-tumor drugs targeting modified enzymes and de-modified enzymes will be performed in order to contribute to future research.